0322 Books, Buildings, and Construction Techniques - Cristiano Guarneri; Ines Ivić (RIHA Journal, 2025)
This paper proposes a methodological model for reconstructing the architectural knowledge present in Dubrovnik during the renovations that followed the earthquake of 1667. Such renovations are seen as a manifestation of both theoretical and practical architectural knowledge, echoing across various sources and evident in the buildings themselves. The authors advocate for a comprehensive approach that integrates the "know-what" of architectural treatises with the "know-how" of sources such as building accounts (libri della fabbrica). Furthermore, they aim to enrich the understanding of Ragusan construction practices by exploring the circulation of knowledge among different construction sites in Dubrovnik and by comparing them with those cultivated in Rome and Venice. This will shed light on the circulation of architectural knowledge, spatial concepts, and decorative styles between Italy and the eastern coast of the Adriatic.